Analisis Dampak Pemutusan Hak Kerja Sepihak Tenaga Pendamping Profesional terhadap Program Pemberdayaan Desa - Dhiya Fahriyyah Maritza; Mawar Mawar (ARISTO, 2026)
This study aims to analyze the impact of unilateral termination of TPP employment rights on the sustainability of village empowerment programs and to emphasize the academic contribution in filling the gap in findings in this field. The research method used is descriptive with a qualitative approach that uses primary data through news that has been reduced to relevant news and secondary data based on journal articles, official reports, and websites. Data analysis uses the Miles and Huberman model based on three stages: (1) reduction (2) verification (3) data presentation and conclusions. The novelty of these findings is that they fill a gap in the literature, which has discussed PHK in a multidisciplinary manner but has not yet researched the aspect of village empowerment. Thus, it can be used as input for policy makers and can make a practical contribution to understanding the implementation of PHK TPP. The results of the study show that PHK TPP has a direct impact on the instability of program implementation, which causes social tension, political pressure, weak work motivation, and significantly hinders the effectiveness of village assistance at the village level, including village fund management. It can be concluded that although these findings contribute to the discussion of the impact of TPP layoffs on village empowerment programs, there are several limitations. This analysis still relies on secondary data, so it does not fully describe the empirical conditions of the stakeholders. Therefore, further research is recommended to use a mixed methods approach and involve the collection of primary data, such as interviews, surveys, and so on, to strengthen the validity of the findings and the relevance of the policy. Keywords: Socio-Political Impact; Program Sustainability; Termination of Employment Rights;  Village Empowerment; Professional Assistants.